Automotive engineering design [electronic resource] : ebook collection - 367294 Blundell, Michael (London : Butterworth-Heinemann, 2008)
Contains of 5 titles -- 1.-- Multibody systems approach to vehicle dynamics /Blundell and Harty -- 2. Motor vehicle structures / by Brown et.al -- 3.Vehicle refinement /by Harrison -- 4. Intelligent vehicle technologies /by Vlacic -- 5. Understand automotive electronics /by Ribbens